Upper Jurassic Hybodontidae (Selachii) from Lourinhã, Portugal - Balbino, A. C. (2010)
Hybodontidae teeth and spines from the Lourinha Formation, Sobral unit are described. These teeth and spines have been ascribed to the genus Hybodus and regarded as Hybodus cf. reticulatus.